Co-seismic and post-seismic deformation for the 1995 Colima–Jalisco and 2003 Tecomán thrust earthquakes, Mexico subduction zone, from modelling of GPS data. Issue 3 (25th October 2021) - Cosenza-Muralles, B; DeMets, C; Márquez-Azúa, B; Sánchez, O; Stock, J; Cabral-Cano, E; McCaffrey, R
SUMMARY: We invert ∼25 yr of campaign and continuous Global Positioning System daily positions at 62 sites in southwestern Mexico to estimate co-seismic and post-seismic afterslip solutions for the 1995 M w = 8.0 Colima–Jalisco and the 2003 M w = 7.5 Tecomán earthquakes, and the long-term velocity of each GPS site. Estimates of the viscoelastic effects of both earthquakes from a 3-D model with an elastic crust and subducting slab, and linear Maxwell viscoelastic mantle are used to correct the GPS position time-series prior to our time-dependent inversions. The preferred model, which optimizes the fit to data from several years of rapid post-seismic deformation after the larger 1995 earthquake, has a mantle Maxwell time of 15 yr (viscosity of 2 × 10 19 Pa s), although upper-mantle viscosities as low as 5 × 10 18 Pa s cannot be excluded. Our geodetic slip solutions for both earthquakes agree well with previous estimates derived from seismic data or via static co-seismic offset modelling. The afterslip solutions for both earthquakes suggest that most afterslip coincided with the rupture areas or occurred farther downdip and had cumulative moments similar to or larger than the co-seismic moments. Afterslip thus appears to relieve significant stress along the Rivera plate subduction interface, including the area of the interface between a region of deep non-volcanic tremor and the shallower seismogenic zone. We compare the locations of the seismogenic zone, afterslip and tremor in our study area to those of the neighbouring Guerrero and Oaxaca segments of the Mexico subduction zone. Our newly derived interseismic GPS site velocities, the first for western Mexico that are corrected for the co-seismic and post-seismic effects of the 1995 and 2003 earthquakes, are essential for future estimates of the interseismic subduction interface locking and hence the associated seismic hazard.